The shard the official guidebook - Powell, Kenneth 1947- (Thames & Hudson, 2013)
Designed by the internationally renowned architect Renzo Piano and developed by Irvine Sellar, The Shard is one of the worlds most striking new skyscrapers and is now, at 310m, the tallest building in Western Europe. From 1 February 2013, people will be able to visit "The View" on floors 68, 69 and 72 almost twice the height of any other viewing gallery in London from where they will experience a 360-degree, 40-mile view over one of the worlds most historic and exciting cities. Organized spread by spread, easy to navigate and as elegantly designed as the building itself, the official guidebook sets The Shard in the context of Southwark, one of the capitals most historic boroughs, before outlining the design principles and construction story of the building. Also included are Q&As with both the architect and the developer and fascinating facts and stats relating to this extraordinary building.Central to the books purpose as the official guidebook are a series of twelve high-resolution double-page panoramic photographs of the views from The Shard (three per compass point: looking left, looking right and looking down), each annotated to identify Londons key buildings, monuments and landmarks. An informative souvenir for visitors to The Shard, the book will also be available in the trade, making it available to all Londoners and visitors to the capital